PRE-SERVICE TEACHERS’ CONCEPTIONS AND COMPETENCES ON DIGITAL LITERACY IN AN EFL ACADEMIC WRITING SETTING - Nabhan, Salim (Universitas Pendidikan Indonesia, 2021)
This case study seeks to examine pre-service teachers’ digital literacy conceptions in an EFL academic writing context and aims to identify pre-service teachers’ competences concerning the predominant dimensions of digital literacy encompassing critical thinking, online safety skills, digital culture, collaboration and creativity, finding information, communication, and functional skills. This case study involved both quantitative and qualitative data taken from 107 pre-service teachers’ online questionnaires and one 5-member focus group discussion delivered to pre-service teachers taking academic writing subjects in English Language Education Department in an urban university in Indonesia. In general, the result of the study revealed that the pre-service teachers’ conceptions of digital literacy were principally associated with the narrow proficiency of utilizing online tools and technological devices and set aside a critical mindset. Further, in spite of the fact that most participating students were found to have lack of understanding of critical thinking and digital culture towards digital literacy, they appeared to possess the competencies of finding information, communication, and functional skills. Additionally, quantitative result of the pre-service teachers’ competences demonstrated that communication dimension was the highest of all with the mean value of 3.95, followed by online safety skills (3.87), finding information (3.79), critical thinking (3.77), functional skills (3.75), as well as collaboration and creativity (3.43). The lowest mean (3.40) belonged to digital culture dimension. The findings have important implications for developing digital literacy framework in an EFL academic writing.